The Influence of the SQ3R Learning Method (Survey, Question, Read, Recall, Review) in Increasing Student Learning Outcomes in Class XI Christian Religious Education Subjects Electrical Engineering at SMK Negeri 1 Merdeka Berastagi - Sinaga, Lorinta Rupmahita; Munthe, Bangun; Siregar, Nurliani (Lembaga Riset Mutiara Akbar, 2025)
The aim of this research is to see the influence of the SQ3R Learning Method (survey, question, read, recall, review) in improving student learning outcomes in Christian Religious Education Subjects Class XI Electrical Engineering at SMK Negeri 1 Merdeka Berastagi. This type of research is classroom action research with the research population being all students of class XI electrical engineering at SMK Negeri 1 Merdeka Berastagi. Where in this research used cycle I and cycle II. After conducting research, in cycle I the average post-test score was 68.28% and the overall learning outcomes of class XI students were 38.09%. This research was continued in cycle II with an average post-test score of 85.71 and overall student learning outcomes of 85.2%. So it was concluded that there was an increase in student learning outcomes using the Influence of the SQ3R Learning Method (survey, question, read, recall, review) in improving student learning outcomes in Christian Religious Education Subjects at SMK Negeri 1 Merdeka Berastagi. During the learning process in the experimental class, observations were made of student learning activities and obtained final grades in the very good category.